Influences of energy management strategy on stress state of near real geometry of turbine disk. (December 2015) - Li, Guo; Ding, Shuiting; Bao, Mengyao
Highlights: The essence of using cooling in turbine systems is a process of energy management. Energy management strategy is proposed to reflect developed cooling technology. The equation correlating energy management strategy with stress for disk is built. Stress state can be controlled by actively adjusting the energy management strategy. The artificial temperature gradient can be used to counteract stress from rotating. Abstract: From the point of view of the physical essence, using cooling technology in turbine systems is a process of energy management and the developed cooling structure in the last forty years is aimed at carrying out a different energy management strategy. Based on this idea, in this paper the energy management strategy for each cooling structure was abstracted first and reflected by parameters of heating energy Q e in the outer surface, exchanged energy Q in in the inner surface and wall heat transfer coefficient h of the disk. Then, the influences of energy management strategy on stress state of near real geometry of the turbine disk were investigated. That is, the equation correlating different energy management strategies with stress states for disks was built by theoretical analysis and the computational fluid dynamics and finite element simulations were applied to validate the theoretical analysis. Results showed that the stress state could be effectively controlled through actively adjusting the energy management strategy. And under a constant cooling structure and equal consumption of cooling air and heating energy conditions, the heating energy of disks could be rearranged (reflected by allocation ratio of heating energy ϕ ) in outer ( Q e ) and inner ( Q in ) surface to achieve the actively heated hub of the disk, and the resulting decline ratio of maximum equivalent stress level in hub could be arrived 45.52% at ϕ = 0.20 to compare with the conventional energy management strategy ( ϕ = 0 ), even in 3981 rpm. The reason for the preceding effect was explained by an artificial V-shaped temperature distribution that was established in the disk through actively rearranging the heating energy and correspondingly, the reverse temperature gradient between the hub and web produced a pulling effect and counteracted parts of the stress from rotating. In general, the simulation data were in strong agreement with the above results.